Oxygen profiles and pore-water geochemistry of surface sediments collected from the southern Weddell Sea shelf - Baloza, Marwa; Maier, Sandra; Hanfland, Claudia; Henkel, Susann; Kasten, Sabine; Richter, Claudio; Holtappels, Moritz (PANGAEA, 2025)
During the PS111 research cruise with the German research vessel RV POLARSTERN (January 2018- March 2018), sediments were collected with a multicorer from 15 stations, i.e., four on the eastern Weddell Sea shelf at 387 to 663 m water depth, five in the Filchner Trough at 794 to 932 m water depth, and four along the western Weddell Sea shelf at 332 to 660 m water depth. Two deeper stations were located on the eastern Weddell Sea slope at 1405 and 1775 m water depth. A total of 28 high-resolution O2 profiles were measured in the upper sediment layer using optical microsensors (Optodes, Pyroscience) in order to determine diffusive oxygen uptake (DOU). Pore-water samples were taken at depth resolutions of 1 cm from 0-10 cm and below 10 cm with a resolution of 2 cm down to a maximum depth of 35 cm. Pore-water analyses of dissolved iron (DFe), manganese (DMn), sulfate (SO42-), and nutrients such as ammonium (NH4+), phosphate (PO43-), nitrate (NO3-), nitrite (NO2-), and silicate (SiO32−) were measured.
Keywords: Antarctic; dissolved iron; dissolved manganese; nutrients; oxygen uptake; shelf sediments